Herlyn–Werner–Wunderlich syndrome: diverse presentations and diagnosis on MRI. Issue 6 (June 2020) - Zhang, H.; Ning, G.; Fu, C.; Bao, L.; Guo, Y.
Abstract : Aim: To evaluate the diverse presentations of Herlyn–Werner–Wunderlich (HWW) syndrome on magnetic resonance imaging (MRI) and its surgical correlations. Materials and methods: From 2014 to 2019, a total of 40 patients with HWW syndrome underwent pelvic MRI. All MRI images were reviewed by two experienced radiologists in consensus. Uterine anomalies, obstruction sites, laterality and communications, urinary anomalies, and other abnormal findings were recorded. MRI findings were correlated with ultrasonography and surgical results. Results: On MRI, the uterus was didelphic in 25 (62.5%), septate in nine (22.5%) and bicornuate in six cases (15%); an ipsilateral vaginal septum was found in 30 cases (75%), and ipsilateral cervical obstruction (obliterated cervical os) was found in 10 cases (25%). Twenty-seven patients underwent surgical treatment. MRI diagnoses of obstruction sites correlated completely with the surgical results. Although obstruction communications could not be found with ultrasonography, MRI identified nine cases of cervical communication, but failed to detect the five cases of surgically confirmed fistula on the vaginal septum. Moreover, MRI identified nine cases of ipsilateral ureteral remnants and/or paravaginal cystic structures, all with insertion into the obstructed vagina or cervix, and one case of ipsilateral ureterocele. Conclusions: HWW syndrome can present as different combinations of uterine anomalies, unilateral cervico-vaginal obstruction, and ipsilateral renal anomalies; ipsilateral paravaginal cystic structures and/or ureter remnants inserting into the obstructed vagina or cervix can occasionally be seen. MRI can provide a comprehensive preoperative evaluation and better identification of obstruction sites, but seems insensitive for detecting vaginal communications in HWW syndrome. Highlights: HWW syndrome is a complex urogenital anomaly with various anatomic presentations. MRI can accurately identify anatomic variants and obstruction sites of HWW syndrome. MRI can identify cervical communications, but is insensitive for detecting vaginal fistulas in HWW syndrome.